L'incidence de la nouvelle Loi sur les assurances sur les régimes matrimoniaux - Fortin-Houle, Christiane; Roy, Madeleine (Les Cahiers de droit, 1978)
On October 20, 1976, a new Insurance Act came into force in Québec. It was expected to solve, among other problems, most of those concerning the relationship between insurance law and matrimonial regimes and the interpretation of the relevant statutory provisions. Unfortunately, only a few articles in the marriage covenants section of the Civil Code were amended. This paper stresses the fact that the main problem in insurance law is the definition of basic elements, such as the policy, the proceeds, the owner and the beneficiary, and that the new act has failed to clarify the meaning of those terms. The paper analyses the notions of policy and proceeds, with regard to the partnership of acquests and the community of moveables and acquests, and comes to the conclusion that, although effective for insurers, the new act has not solved problems raised by the cases and the authorities.